Efectos de un programa de comprensión lectora en estudiantes de cuarto de primaria de una institución educativa del Callao - Salinas Mariñas, Jacqueline (2010)
The purpose of the research was to demonstrate the effectiveness of a stimulation program for reading comprehension proposed by Velarde, it was applied to a sample of 48 students composed of children from 9 - 11 years old of fourth grade of primary education in a educational institution of Callao, which evaluation was conducted in two phases: pre-test and post-test, with the instrument PROLEC by Cueto, Rodriguez y Ruano. It was noted that syntactic processing favors the acquisition of semantic process, being grammatical structures in compared to the punctuation marks, which contributed significantly to the understanding of sentences and texts. In data processing, we use the statistic T of Student test in which we could observed in the experimental group a mean of 39.6 +7.6 in the pre-test in the Reading Comprehension and in the post-test an average of 43.8 +5.7, demonstrating an increase in the statistically significant mean of 0.000, showing that the stimulation program is effective and improve the reading comprehension.